Bibliometric analysis of Latin American scientific journals of Psychology through the Scimago portal - Vizioli, Nicolás Alejandro (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
The preference for English as the language of scientific publications has resulted in a greater number of citations and a higher level of esteem for English-language scientific journals compared to those published in other languages. Consequently, researchers are frequently compelled to select a language other than their native tongue in which to disseminate their findings. This study sought to examine the extent and quality of coverage of Latin American psychology journals. A bibliometric analysis of scientific journals was conducted via the Scimago portal, with consideration given to the membership quartile based on the SJR indicator. It was determined that publications from Latin America account for 3.52% of the total coverage on Scopus (n=1336). The distribution of journals across the quartiles is as follows: 80.85% are located in quartile 4, while 19.15% are in quartile 3. A total of 85.11% of Latin American journals are open access. In the context of Latin America, Brazil is the country that exhibits the highest level of coverage and performance. In general, the results indicate that, although the coverage is less extensive than in other regions, the majority of Latin American publications are open access, facilitating rapid access to information.